Seasonal abundance of the Monte Albo cave salamander Speleomantes flavus in Italy - Luca Coppari; Enrico Lunghi (Subterranean Biology)
The Monte Albo cave salamander, Speleomantes flavus, is the species endemic to the namesake massif located in the northeastern part of Sardegna, Italy. Speleomantes are the only plethodontid species in Europe, a genus composed of eight troglophilic species living in epigean and subterranean environments. Most ecological studies on these species deal with species occupancy (i.e., presence/absence), while studies aiming to identify drivers for their abundance are lacking. Here, we present the first study aiming to determine which ecological factors influence the abundance of S. flavus. We identified three main hypotheses: (1) salamanders are more abundant where microclimatic conditions are the most suitable for their physiological requirements; (2) Speleomantes are more abundant where prey richness is the highest; and (3) salamanders tend to avoid potential predators. Our results suggested that cave air temperature, humidity, and illuminance are strongly affected by season, and individuals of S. flavus tended to aggregate in relatively cold and humid areas not far from the cave entrance. For most Speleomantes, there was a significant correlation between their abundance and the presence of the considered invertebrate species. This study produced the first information on which ecological features affect the abundance of S. flavus individuals. Additional studies extending to further Speleomantes populations and species may support our hypotheses, including factors not considered here.